Akuntabilitas Kinerja Program Bantuan Stimulan Perumahan Swadaya (BSPS) di Dinas Perumahan Rakyat Kawasan Permukiman Perhubungan dan Pertanahan Kabupaten Boalemo - RAF, Balada (Universitas Islam Darul Ulum Lamongan, 2024)
This study aims to determine the Performance Accountability of the Self-Help Housing Stimulus Assistance Program (BSPS) at the Public Housing, Residential Areas, Transportation and Land Agency of Boalemo Regency. The type of research that the author uses is a descriptive type with a qualitative approach, where descriptive research. This research method uses qualitative research conducted during data collection and after data collection is completed in a certain period. With interview techniques, researchers analyze the answers of the interviewees. Activities in data analysis, namely data reduction, data display and conclusion and drawing/verification. The results of the research on the Performance Accountability of the Self-Help Housing Stimulus Assistance Program (BSPS) at the Public Housing, Residential Areas, Transportation and Land Agency of Boalemo Regency can be said to be quite successful with several indicator approaches, namely Accountability of Agency Performance in BSPS Tasks, Equalization of Opportunities for BSPS Programs, Accountability Reports for Apparatus Performance in the BSPS program, Work Results in the BSPS program, however, there are still several weaknesses in the process and procedures for determining recipients so that they need to be refined to be more targeted and objective.